Ḥadith ‘Āishah fī Man’i al-Nisā’ Min al-Masājid; Niqāsh ‘Ulamā’ Bangladesh Ḥaulahu - Syed Mahmudul Hasan (JOURNAL OF QUR'AN AND HADITH STUDIES, 2020)
The Narration of Aisyah (May Allah be pleased with her), is the main focus of the controversy among Bangladeshi scholars on the issue of women's prayer in the mosque. The reason for the dispute is that a group of them issued the ruling based on the phenomenon of the text, and the others explained the ruling of Hadith according to the common situation in the society. If the circumstances change, the ruling will change along with it, because the originality of the issue is permissible, that is proven from other texts. This research adopts an inductive method to survey the Prophetic hadiths that talk about the prayer of women in the Mosque in terms of permissibility and prohibition and analytical method to analyze the difference in opinion of Bangladeshi scholars related to this issue. The research finds that the ruling of Shari’ah is a process that is continuous and permanent. But in necessity and emergency, it has the notion of flexibility and explanation. In the issue of women’s presence in the mosque, they should be allowed if they abide by the suggestions of Prophet (s) and should not if they don’t. So, Prohibition is not from the prophet (s), but it is from their obedience to the ruling.